Identification of palliative care requirement in hospital inpatients in internal medicine services in a peruvian reference hospital: Identificación de requerimiento de cuidados paliativos en pacientes hospitalizados en los servicios de medicina interna de un hospital de referencia peruano - Velasquez-Manrique, Annie (2023)
Introduction: Hospitals of greater complexity tend to care for patients with advanced chronic diseases, which is why it is important to recognize the need for palliative care. Objective: To identify the proportion of patients who require palliative care in the medicine department of a Peruvian referral hospital. Methods: Observational, analytical, cross-sectional study. All hospitalized patients were studied in the Department of Internal Medicine of the Peruvian hospital during the period April-May 2018. To determine the need for palliative care, the NECPAL CCOMS-ICO © instrument was used. The quantitative variables are presented as median and interquartile range (IQR); and numerical variables, such as frequencies and percentages. For the comparison of numerical variables, the Mann Whitney test was used and the chi-square test for categorical variables.  Results: They were evaluated in 281, where 102 (37.9%) required palliative care. The median age in patients requiring palliative care was 69.5 (IQR: 58-81) years. The median hospital stay in patients with and without the need for palliative care was 7 days (IQR: 4-11) and 9 days (IQR: 5-19) respectively, the mortality in patients with and without the need for palliative care was 37.25% and 4.19% respectively. Conclusions: There is a high frequency of need for palliative care in patients hospitalized in internal medicine wards, the requirement for palliative care was associated with higher mortality and hospital stay, which evidences the need for comprehensive and personalized care based on medical services specialized.